Impact of Programmed Death Ligand 1 Expression in Advanced Non-Small–Cell Lung Cancer Patients, Treated by Chemotherapy (GFPC 06-2015 Study) - Auliac, Jean-Bernard (Onco Targets Ther, 2020)
BACKGROUND: Few data have been published on the clinical and histopathological characteristics of advanced non-small–cell lung cancer (NSCLC) patients with high PD-L1 expression versus intermediate or none and the prognostic value of PD-L1 expression for patients treated with chemotherapy is unknown. This study was undertaken to prospectively assess the prognostic value of tumor-cell (TC) and immune-cell (IC) PD-L1 expressions for advanced NSCLC patients. METHODS: It was a prospective, multicenter study on advanced NSCLC patients, with performance status 0/1, scheduled, consecutively, to receive first-line platin-based chemotherapy. PD-L1 expression was determined immunochemically (Dako Autostainer and monoclonal antibody 22C3) and its impact on progression-free survival (PFS) and overall survival (OS) assessed. RESULTS: Among 198 patients screened in 19 centers, 140 were included median age: 66.5 ± 10 years; 76.4% men; 79.3% Caucasians; 10.7% nonsmokers; 63.6% adenocarcinomas; <1%, 1–50% and ≥50% TC PD-L1–expression rates were 47.1%, 25.7% and 27.2% of patients, respectively; respective null, intermediate and high rates on ICs were 35.7%, 38.6% and 25.7%. Second- and third-line chemotherapies were administered to 58.6% and 26.4% of the patients, respectively. None received immunotherapy. First-, second- and third-line median (95% CI) PFS lasted 4.6 (3.6–5.2), 3.7 (2.3–4.7) and 2.2 (1.5–4.3) months, respectively; median OS was 16.9 (11.4–19.9) months. No significant PFS and OS differences were observed according to TC or IC PD-L1 expression. CONCLUSION: According to the results of this prospective, multicenter study, neither TC nor IC PD-L1 expression appears to be prognostic for chemotherapy-managed advanced NSCLC patients.